2008
DOI: 10.1509/jmkg.72.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Do Frontline Mechanisms Matter? Impact of Quality and Productivity Orientations on Unit Revenue, Efficiency, and Customer Satisfaction

Abstract: This study identifies a frontline mechanism comprising autonomy, cohesion, and feedback that helps explain when and why the simultaneous pursuit of quality and productivity orientations has positive or negative effects on unit revenue, efficiency, and customer satisfaction. An empirical test of the proposed framework using data from 423 employees in 30 strategic business units and longitudinal unit-level performance data indicates that frontline autonomy mediates the positive impact of productivity and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 71 publications
7
109
0
Order By: Relevance
“…As we have noted, while a dual strategy is desirable, it is particularly difficult to achieve for service organizations (Anderson et al 1997;Marinova et al 2008;Rust and Huang 2012;Singh 2000). To explore potential ways to achieve CESE, we examine next the root causes underlying the service excellence-productivity conflict by integrating the service quality and productivity literature.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…As we have noted, while a dual strategy is desirable, it is particularly difficult to achieve for service organizations (Anderson et al 1997;Marinova et al 2008;Rust and Huang 2012;Singh 2000). To explore potential ways to achieve CESE, we examine next the root causes underlying the service excellence-productivity conflict by integrating the service quality and productivity literature.…”
Section: Empirical Evidencementioning
confidence: 99%
“…These two approaches conflict because too strong a focus on cost reduction associated with productivity can reduce customer satisfaction, and concentration on customer satisfaction is assumed to cost more, thereby reducing productivity (Rust and Huang 2012). Research in marketing has confirmed this tradeoff (Anderson et al 1997;Rust and Huang 2012), and it has been shown to be more pronounced in services than in goods, especially when frontline employees are involved (Anderson et al 1997;Marinova et al 2008;Singh 2000). In addition to the intangibility and variability of services that make them more difficult to standardize (Chase 1978;Frei 2006), perceived quality in services frequently depends on customization desired by consumers.…”
mentioning
confidence: 99%
“…With relationship marketing, organizations try to form long-term alliances with customers by using "a combination of customized products, customized communication, and customized service and delivery-in effect, treating each customer as a unique segment of one". Marinova et al (2008) maintain SQ as an evolutionary process that begins prior to transaction takes place and continues even after the exchange. Taris and Schreurs (2009) emphasized customer satisfaction as the result of value creation by satisfied and loyal workforce of the unit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars dully recognize the importance of quality orientation for service sector organizations. According to them, quality orientation is an important tool that helps achieve competitive advantage, yet it is one of the least researched topics, especially in the service sector [5]. The service sector, by and large, capitalizes upon its human resource to achieve and sustain competitive advantage.…”
Section: Introductionmentioning
confidence: 99%